Priorities of Digital Economy Development in Banks of Uzbekistan - Umurzakova Adiba Ochilovna (Genius Journals, 2022)
The main purpose of the scientific article is to provide conclusions and recommendations on priority issues such as the widespread introduction of modern information and communication technologies in the banking system of the Republic, automation of business processes of commercial banks and creating the necessary conditions for expending remote banking services. This scientific article describes the theoretical and praсtical basis for the use of banking services in the system bank settlements, the factors contributing to it, the practical measures taken by commercial banks in this direction.
Keywords: digital economy; banking system; electronic money; payment systems banking